Latino Pentecostal identity : evangelical faith, self, and society - Sánchez-Walsh, Arlene M. (Columbia University Press, 2003)
-- Benjamin Ortiz, In These Times.
Keywords: Hispanic American Pentecostals.; RELIGION -- Messianic Judaism.; RELIGION -- General.; Hispanic American Pentecostals